Utilização de derivativos financeiros na gestão de risco pelas cooperativas agropecuárias do Estado do Paraná Brasil - Souza, Claudemir José de (2013)
In recent decades, studies on the management of risk through instruments such as derivatives have become frequent and many issues related to these instruments remain. Understanding the different classes of risk in which the agricultural cooperatives are exposed will cause financial managers use derivatives and other suitable methodologies for effective management in order to meet the thesis defended by the theory of Finance that the use of derivatives should have preferably the purpose of protecting the organization from risks and not be just another way to obtain results with speculative purposes. This study aimed to investigate the risk management in a sample of 47 agricultural cooperatives in the State of Paraná. Regarding the methodology used descriptive explanatory research with the application of a questionnaire sample financial managers. The evidence showed that the managed risk classes with more derivatives managed by financial managers of cooperatives are foreign exchange exposures, followed by commodities, interest rate and equity not following the same order of other surveys conducted in Brazil and abroad as well as showed that the biggest concern of financial managers is linked to institutional and legal aspects than financial. The knowledge and the management of the risks inherent to the activity in agricultural cooperatives in the State of Paraná have been contributing in the affirmative showing the constant need for improvement in the management of these organisations for the benefit of cooperative members, and consequently, for the good of society as a whole